Evaluasi Kinerja High Availability Firewall pfSense Menggunakan CARP pada Jaringan LokaL - Ade Frihadi; Silviana Windasari; Abdurohman Abdurohman (Pusat Riset dan Inovasi Nasional, 2026)
The availability of network services is a crucial factor in supporting organizational activities, particularly in environments that rely on continuous network connectivity. Disruptions to firewall devices can cause the entire network service to stop, as firewalls function as the central point for security enforcement and traffic management. One solution to address this issue is the implementation of a High Availability (HA) mechanism. This study aims to evaluate the performance of a High Availability system on a pfSense firewall using the Common Address Redundancy Protocol (CARP) in a local network environment. The research method employed is an experimental approach by deploying two pfSense devices configured in a master–backup scheme. Testing was conducted by simulating failures on the primary firewall and measuring network performance parameters, including failover time, packet loss, delay, and connection stability during the service transition process. The results show that the implementation of CARP on the pfSense firewall is capable of performing automatic failover with relatively short service switching time and minimal network disruption. Network connectivity can be well maintained, particularly for TCP-based services, indicating that this High Availability system is effective in improving the reliability and availability of local networks. This study is expected to serve as a reference for implementing pfSense-based redundant firewall systems in small- to medium-scale network environments.